Desain Sistem Kontrol LQIT-Gain Scheduling PID untuk Way Point Tracking Control Quadrotor UAV - Aditya Eka Mulyono; Aris Triwiyatno; Sumardi (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2014)
Quadrotor is an unmanned aerial vehicle which has ability to accomplish difficult missions like surveilance from the sky, search for natural disaster victims, and saving mission. To accomplish that missions, a quadrotor must be able to fly stable and can be directed to desired direction. For that purpose a control system absolutely needed to a quadrotor system. In this research a control system was designed to stabilized a quadrotor and could be directed to did way point tracking. LQIT-PID gain scheduling was proposed to make quadrotor be able to track the way point. Linear Quadratic Integral Tracking method was used to stabilized atittude of a quadrotor, PID was used to control the position of a quadrotor, and gain scheduling mechanism was used to scheduled PID parameter that change depends on the change of range between way point when the first tracking begin. Simulation results shown that this method could make quadrotor do the way point tracking task, but for several condition, it could make quadrotor unstable to fly.